SCDSP: a novel stream cipher with dynamic structure and parameters - Mohamed Eljadi, Fardous; Alyaseen, Imad Fakhri Taha (Convergence Information Society(CIS), 2015)
A few dynamic design stream ciphers have been described in a number of papers. Moreover, the majority of these papers are just focused on dynamic polynomial switching in the Linear Feedback Shift Registers. This paper proposed a novel stream cipher with dynamic structure, which is based on using dynamic parameters to increase the complexity of the cipher. In the proposed cipher, the dynamic parameters are the number of registers, the length of registers, clocking system, initialization procedure, confusion and diffusion method, and output function. These parameters are specified using bits from the secret key. The National Institute of Standards and Technology (NIST) suite is used to evaluate the randomness of the proposed design, and the results are encouraging.